If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4y+48=-7(y-6)
We move all terms to the left:
-4y+48-(-7(y-6))=0
We calculate terms in parentheses: -(-7(y-6)), so:We get rid of parentheses
-7(y-6)
We multiply parentheses
-7y+42
Back to the equation:
-(-7y+42)
-4y+7y-42+48=0
We add all the numbers together, and all the variables
3y+6=0
We move all terms containing y to the left, all other terms to the right
3y=-6
y=-6/3
y=-2
| 11/3=8/x | | 83.5=3.5x-60 | | 180-(x+10)=2x+2x | | 18x=18x-11 | | (2x-14)+(-6+8×)=180 | | -2(c-11)+6=-8c-2 | | 5(2y-1)+y=39 | | 4x+30-2x+54=90 | | 5/8=n/11 | | 65=35^z | | 8(4u-1)-12u=11(2u-6 | | 5=7-h | | (x+4)/4=3/2 | | 2x-6÷12=0 | | 4+x=7-6 | | 4(s-2)-3=s+1 | | -4(x-7)=-7x+19 | | 1/10=x/7 | | -8x-6=-10x-22 | | x²+9=3x+139 | | p-(p+4)=4(p-1)+4 | | 3.14*3*r^2=1846.32 | | 3.14*3*r2=1846.32 | | 6/14=7/(x+3) | | 6/14=7/x+3 | | 7(p+3)=-14 | | -6x+2=-5x+4 | | 12b+10=11b-4 | | 3/5+g=3/10 | | 3x-2/x+4=8 | | Y=3.5x×37-60 | | 12b+10=7b-4 |